Product Quality Control of Tempe: Case Study at Tempe Super Sumber Mas Home Industry Jember (Jurnal Strategi dan Bisnis, 2021)
Abstract This study aims to describe the process of controlling the quality of tempe products carried out by the Tempe Industri rumah tangga Super Sumber Mas which is engaged in the production of Tempe. Product Quality control is important so that product quality results can be maintained and company goals can be achieved. This research uses descriptive qualitative research type. The analysis used is taxonomic analysis. Information gathering is done by observation, interview and documentation. The results showed that the control was carried out at the input, process and output stages. At each stage it has been carried out according to the standards desired by the company, but there are deviations at the process stage, namely when the removal of the foam and skin in the boiling stage is inaccurate, causing damage to the Tempe. Keywords: Quality Contol, Product Quality, Tempe Super Sumber Mas